Building a software tool for transparent and efficient process assessments in IT service management - Shrestha, A.; Cater-Steel, A.; Toleman, M.; Tan, Wui-Gee (Springer International Publishing, 2014)
Abstract. Process improvements provide a structured approach for organisations to improve the way they operate. A number of process improvement methodologies such as ISO9000, TQM, Six Sigma, Lean, and Agile have been proposed over the last few decades and subsequently software tools have been developed to apply these methodologies. However determination of process capability to measure improvement is predominantly conducted by expert process assessors and consultants with proprietary frameworks. We propose the use of the international standard for process assessment ISO/IEC 15504 for a transparent measurement of process capability. We also demonstrate development of a software tool based on the standard that can facilitate organisations to assess their processes efficiently. In this paper, we explain the development, implementation and preliminary evaluation of a software-mediated process assessment approach in the area of IT Service Management at a large public-sector IT organisation in Queensland, Australia. This paper's contribution is the integration of the design science research methodology with the task-technology fit theory for the development of the software tool as a research artefact. For practitioners the project demonstrates transparent and efficient assessment of IT service processes to facilitate continual improvement.